CHINESE YEWELLERY MARKET: EVOLUTION, CURRENT CONDITION AND KEY TRENDS IN DEVELOPMENT - Svetlana V. Zolotova; Svetlana A. Nikolicheva (Вестник Российского экономического университета имени Г. В. Плеханова)
Geographic location and history stipulate the development of close trade contacts between Russia and the Chinese People's Republic, including the sphere of yewellery trade. However, it should be mentioned that due to many reasons a lot of aspects connected with functioning of precious metal goods market in China have not been highlighted in research of Russian authors. In spite of the fact that the country is the second biggest economy in the world and takes the leading position in the list of foreign trade partners of Russia, information about the situation in yewellery industry of China is very limited. It can sound strange, especially if we take into account the fact that in 2014 China became the world leader both in production and consumption of gold and its share of consumption of yewellery goods made 41,2%. More and more overseas companies are expanding to the Chinese market. The authors show that China with its promising market of yewellery goods could become a profitable partner for the Russian Federation.